PERAN HARGA DIRI DALAM MEMEDIASI HUBUNGAN ANTARA PERBANDINGAN SOSIAL DAN KECEMASAN SOSIAL PADA REMAJA YANG TINGGAL DI PANTI ASUHAN - Jihan Rahma Diadiningrum; Setiasih Setiasih (Program Studi S1 Psikologi, 2023)
Adolescents who live in orphanages have a greater risk of experiencing social anxiety problems than adolescents who live with their families. Social anxiety arises from the intensity of high social comparisons and is followed by low self-esteem in adolescents. This study aims to examine the mediating role of self-esteem in the relationship between social comparison and social anxiety in adolescents living in orphanages. The training was conducted on 124 youths living in orphanages aged 13-18 years. The research instrument used a social anxiety scale, the Rosenberg Self-Esteem Scale (RSES) and the Iowa Netherland Comparison Orientation Measure (INCOM). The data was processed by mediation analysis using the statistical program JASP version 0.14. As a result, self-esteem can act as a mediator of the relationship between social comparison and social anxiety in adolescents living in orphanages.